The CYB5R3 c . 350C >G and G6PD A alleles modify severity of anemia in malaria and sickle cell disease - Gordeuk, Victor R.; Shah, Binal N.; Zhang, Xu; Thuma, Philip E.; Zulu, Stenford; Moono, Rodgers; Reading, N. Scott; Song, Jihyun; Zhang, Yingze; Nouraie, Mehdi; Campbell, Andrew; Minniti, Caterina P.; et al. (American journal of hematology, 2020)
Genetic modifiers of anemia in Plasmodium falciparum infection and sickle cell disease (SCD) are not fully known. Both conditions are associated with oxidative stress, hemolysis and anemia. The CYB5R3 gene encodes cytochrome b5 reductase 3, which converts methemoglobin to hemoglobin through oxidation of NADH. CYB5R3 c.350C > G encoding CYB5R3 T117S , the most frequent recognized African‐specific polymorphism, does not have known functional significance, but its high allele frequency (23% in African Americans) suggests a selection advantage. Glucose‐6‐phosphate dehydrogenase (G6PD) is essential for protection from oxidants; its African‐polymorphic X‐linked A+ and A‐ alleles, and other variants with reduced activity, coincide with endemic malaria distribution, suggesting protection from lethal infection. We examined the association of CYB5R3 c.350C > G with severe anemia (hemoglobin <5 g/dL) in the context of G6PD A+ and A‐ status among 165 Zambian children with malaria. CYB5R3 c.350C > G offered protection against severe malarial anemia in children without G6PD deficiency ( G6PD wild type or A+/A‐ heterozygotes) (odds ratio 0.29, P = .022) but not in G6PD A+ or A‐ hemizygotes/homozygotes. We also examined the relationship of CYB5R3 c.350C > G with hemoglobin concentration among 267 children and 321 adults and adolescents with SCD in the US and UK and found higher hemoglobin in SCD patients without G6PD deficiency (β = 0.29, P = .022 children; β = 0.33, P = .004 adults). Functional studies in SCD erythrocytes revealed mildly lower activity of native CYB5R3 T117S compared to wildtype CYB5R3 and higher NADH/NAD+ ratios. In conclusion, CYB5R3 c.350C > G appears to ameliorate anemia severity in malaria and SCD patients without G6PD deficiency, possibly accounting for CYB5R3 c.350C > G selection and its high prevalence.